2023
DOI: 10.1097/01.naj.0000911540.75111.b4
|View full text |Cite
|
Sign up to set email alerts
|

Addressing CAUTIs with an External Female Catheter

Abstract: A CNS-led initiative to achieve better patient outcomes-at a significantly lower cost.U rinary tract infections (UTIs) are one of the most common types of health careassociated infections and account for more than 30% of infections in acute care hospitals. 1 Most health care-associated UTIs are caused by indwelling urinary catheters. Also known as a Foley catheter, an indwelling urinary catheter is a drainage tube inserted into the urinary bladder through the urethra; the other end of the tube is connected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Cost-Effectiveness 6 30,38,49,51,52,57 Analyses have shown potential savings associated with FEUWD use through the avoidance of toilet-related falls and reduction in time required for incontinence care. Individual institutions have also generated their own estimates of cost savings, ranging from $13,786 on a per-patient basis to $1 million per year at a large academic hospital due to reduced CAUTIs and Medicare fines.…”
Section: Little Difference Between Feuwds and Iucs (Depends On Method)mentioning
confidence: 99%
See 3 more Smart Citations
“…Cost-Effectiveness 6 30,38,49,51,52,57 Analyses have shown potential savings associated with FEUWD use through the avoidance of toilet-related falls and reduction in time required for incontinence care. Individual institutions have also generated their own estimates of cost savings, ranging from $13,786 on a per-patient basis to $1 million per year at a large academic hospital due to reduced CAUTIs and Medicare fines.…”
Section: Little Difference Between Feuwds and Iucs (Depends On Method)mentioning
confidence: 99%
“…Patient and Nurse Satisfaction 8 22,24,26,28,30,35,38,68 Satisfaction was high. Studies indicated good patient and caregiver satisfaction with home, outpatient community, and hospice care use of PureWick.…”
Section: More Data Neededmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications from catheter-associated urinary tract infections (CAUTIs) can extend hospital stays, cause patient discomfort, and raise medical expenses and death. 1 Meanwhile, catheterization of the urinary tract is a routine hospital operation with a high risk of hospital-acquired urinary tract infections (UTIs). It is responsible for over 70% of all UTIs.…”
Section: Introductionmentioning
confidence: 99%